2019
DOI: 10.1021/acsearthspacechem.8b00209
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Gas-Phase Organohalogens from Aqueous Photochemistry Using Orbitrap Mass Spectrometry

Abstract: Marine short-lived halogenated compounds, emitted from algae, phytoplankton and other marine biota, affect significantly both the troposphere and the stratosphere. Here we show that such compounds might also be photochemically produced through photosensitized reactions in surface water. Gas-phase products were detected and identified by high-resolution mass spectrometry, more particularly by means of an atmospheric pressure chemical ionization (APCI) source coupled to an Orbitrap mass spectrometer. Under simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Particle formation was observed for CAT 8 and GP 10 SML samples. Results from the atmospheric simulation experiments conducted on SML samples were in agreement with previous laboratory studies that demonstrated air-sea interfacial driven chemistry as a source of marine secondary aerosol (Roveretto et al, 2019;Ciuraru et al, 2015;Fu et al, 2015).…”
Section: Soa Formation Potency From Sml Samplessupporting
confidence: 88%
See 1 more Smart Citation
“…Particle formation was observed for CAT 8 and GP 10 SML samples. Results from the atmospheric simulation experiments conducted on SML samples were in agreement with previous laboratory studies that demonstrated air-sea interfacial driven chemistry as a source of marine secondary aerosol (Roveretto et al, 2019;Ciuraru et al, 2015;Fu et al, 2015).…”
Section: Soa Formation Potency From Sml Samplessupporting
confidence: 88%
“…21 and 34) that were identified as halogenated compounds were enriched in SML samples (Table S4). Possible sources of halogenated compounds in SML samples are photochemical reactions occurring at the water/air interface (Roveretto et al, 2019;Donaldson and George, 2012). It is worth noting that organic compounds identified in the discriminant panel may have derived both from the secreted (exometabolome) and/or intracellular metabolites (endometabolome) of biological organisms such as algal species and microorganisms present in seawater.…”
Section: Discriminant Compound Identification and Role In Aerosol Partimentioning
confidence: 99%
“…The predicted maxima are shifted towards higher halide concentrations compared with our observations. This can be explained if CA derived radicals reacted with halogen radicals to produce halogen-containing organic compounds, as already observed in aquatic media (Roveretto et al, 2019), which could result in a partial scavenging of halogens. Another feature captured by our model is the fact that the downward slopes of observed HO 2 production are greater for films containing bromide than for those containing iodide.…”
Section: Ho 2 Production Scavenging and Releasementioning
confidence: 72%
“…De Laurentiis et al (2012) suggested that excited triplet states could oxidize bromide faster than OH radicals in seawater. Some modeling studies of aerosol chemistry consider inorganic halogen chemistry to be important (Sherwen et al, 2016b, a); however, Pechtl et al claimed that reactions with dissolved organic matter may be included as a relevant HOI deactivation pathway (Sarwar et al, 2016;Pechtl et al, 2007;Roveretto et al, 2019). Photosensitized halogen activation is less understood and has not been included in these models.…”
Section: P Corralmentioning
confidence: 99%
See 1 more Smart Citation